Hubungan Praktik Buang Sampah dengan Kejadian Demam Berdarah Dengue di Semarang - Juliana Purdianingrum; Nur Endah Wahyuningsih; Retno Murwani (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Dengue Hemorrhagic Fever (DHF) is one of the major public health problems in Indonesia. The disease is caused by the Dengue virus and is transmitted through the bite of Aedes aegypti and Aedes albopictus mosquitoes. DHF has spread widely throughout Indonesia, one of which is Semarang City and surrounding areas. From the year 2014 to 2015, the number of DHF Incidence Rate (IR) in Semarang City has increased and has decreased in the year 2016. However, dengue cases always appear especially in endemic areas such as Semarang City. This study aimed to analyze the correlation of waste disposal practices with the incidence of DHF in Semarang. This studywas an observational analytic type research with case control approachment. The sample of case group in this study were DHF patients in at three hospitals in Semarang City from March to May 2017 and the control group were healthy people or neighbors from DHF patients living in Semarang, Kendal District and Demak District. The sample was 27 cases and 27 controls using consecutive sampling technique. The data was processed by chi-square test. From the statistical test, it is found that there was no correlation between waste disposal practice (p = 0,091) with the incidence of DHF in Semarang.